2012
DOI: 10.1007/s00439-012-1170-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of smoking and depression

Abstract: Smoking and depression are significant public health problems with multiple etiological dimensions and outcomes. Although each condition is important by itself, they are important because they often potentiate each other. Consequently, it is also essential to understand the nature their relationship. This representative review focuses on the genetic etiology of the relationship in the context of reviewing first the epidemiology of depression and smoking, and then by exploring behavioral and molecular genetic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 118 publications
(124 reference statements)
2
31
0
Order By: Relevance
“…Similar to our results, the aforementioned intervention study in Basel showed that smokers with a history of depression or current use of antidepressants were less likely to quit [34]. This may be related to common genetic mechanisms behind smoking initiation, nicotine dependence and depressive disorders [36,37]. According to the European Respiratory Society-Task force guidelines, respiratory patients who smoke are a difficult target group for smoking cessation, as they tend to minimise their own perceived risk of disease.…”
Section: Health-related Predictors Of Smoking Cessationsupporting
confidence: 85%
“…Similar to our results, the aforementioned intervention study in Basel showed that smokers with a history of depression or current use of antidepressants were less likely to quit [34]. This may be related to common genetic mechanisms behind smoking initiation, nicotine dependence and depressive disorders [36,37]. According to the European Respiratory Society-Task force guidelines, respiratory patients who smoke are a difficult target group for smoking cessation, as they tend to minimise their own perceived risk of disease.…”
Section: Health-related Predictors Of Smoking Cessationsupporting
confidence: 85%
“…the first type is associated with mood disorders and the STin2 polymorphism, and the second type occurs independently from mood disorders and STin2 polymorphism but is associated with a TUD family history. These findings extend those of previous reports showing that the comorbidity between depression/bipolar disorder and TUD may reflect shared neurobiological endophenotypes (Tsuang et al, 2012). Thus, common genetic familial factors may be related to a life history of TUD and depression (Kendler et al, 1993).…”
Section: Tablesupporting
confidence: 79%
“…Potential mechanisms underlying the relationship between TUD and mood disorders, either bipolar disorder or depression, may be explained by common risk factors, including environmental and genetic factors or gene by environmental interactions (Heffner et al, 2011;Kendler et al, 1993;Lyons et al, 2008;McCaffery et al, 2008;Tsuang et al, 2012). Likewise, the comorbidity between both disorders is thought to be determined at least in part by neurobiological endophenotypes (Tsuang et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations